Weight-Related and Personal Risk Factors of Carpal Tunnel Syndrome in the Northern Finland Birth Cohort 1966 - Lampainen, Kaisa; Shiri, Rahman; Auvinen, Juha; Karppinen, Jaro; Ryhänen, Jorma; Hulkkonen, Sina (Journal of Clinical Medicine, 2022)
Background: Excess body mass is a risk factor for carpal tunnel syndrome (CTS), but the mechanisms of this are unclear. This study aimed to evaluate the association between CTS and personal risk factors of body mass index (BMI), waist circumference and waist-to-hip ratio (WHR). Methods: The study sample consisted of the Northern Finland Birth Cohort 1966 (n = 9246). At the age of 31 in 1997 and at the age of 46 in 2012, the participants underwent a clinical examination. Cohort A consisted of complete cases with a follow-up from 1997 to 2012 (n = 4701), and Cohort B was followed up from 2012 to 2018 (n = 4548). The data on diagnosed CTS were provided by the Care Register for Health Care until the end of 2018. Results: After an adjustment for confounding factors, BMI was associated with CTS among women (hazard ratio (HR) 1.47, 95% Cl 0.98-2.20 for overweight women and HR 2.22, 95% Cl 1.29-3.83 for obese women) and among both sexes combined (HR 1.35 95% Cl 0.96-1.90 for overweight and HR 1.98 95% Cl 1.22-3.22 for obese participants). Neither waist circumference nor WHR was associated with CTS. Conclusions: BMI is an independent risk factor for CTS and is more relevant for estimating the increased risk of CTS due to excess body mass than waist circumference or WHR. Peer reviewed